Improving the Ability of Subtraction Count Operations Using Abacus Media for Children with Mild Mental Disability - Adhani Indah Sari; Damri Damri (Universitas Muhammadiyah Enrekang, 2023)
Abstract The background of this research was the discovery of a class VII mild mental retardation child at SLB Perwari Padang who had difficulty learning arithmetic subtraction operations. Based on this, a formulation of the research problem was put forward, namely